2015
DOI: 10.1128/aem.00149-15
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabolism of Exopolysaccharides from Probiotic Lactobacilli by the Human Gut Symbiont Bacteroides thetaiotaomicron

Abstract: bProbiotic microorganisms are ingested as food or supplements and impart positive health benefits to consumers. Previous studies have indicated that probiotics transiently reside in the gastrointestinal tract and, in addition to modulating commensal species diversity, increase the expression of genes for carbohydrate metabolism in resident commensal bacterial species. In this study, it is demonstrated that the human gut commensal species Bacteroides thetaiotaomicron efficiently metabolizes fructan exopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…In order to determine which polysaccharide utilization loci (PULs) within the B. thetaiotaomicron genome are induced to be expressed an produced as proteins in response to GOS, we took the culture supernatants after growth and analyzed for proteins and enzymes using mass spectrometry as has been previously described30. Previously it was found that B. thetaiotaomicron consumes hMOS using a distinct set of pathways attributed to mucin-O-glycan utilization15 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to determine which polysaccharide utilization loci (PULs) within the B. thetaiotaomicron genome are induced to be expressed an produced as proteins in response to GOS, we took the culture supernatants after growth and analyzed for proteins and enzymes using mass spectrometry as has been previously described30. Previously it was found that B. thetaiotaomicron consumes hMOS using a distinct set of pathways attributed to mucin-O-glycan utilization15 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Higher DP GOS compounds are metabolized by an endo-galactanase BtGH53, while small DP2 and branched GOS trisaccharides acted as potential inducers for the expression of mucin glycan degradation PUL-encoded systems in B. thetaiotaomicron . This was indicated by the presence of SusC and SusD homologs in B. thetaiotaomicron culture supernatants which correlated with the bacterium expressing transporters that are involved in the uptake of specific products of glycan degradation1430.…”
Section: Discussionmentioning
confidence: 98%
“…Lactic acid bacteria employ glucansucrase enzymes (e.g., GtfA) to synthesize ␣-glucans with various glycosidic linkages from sucrose or GtfB enzymes to convert starch into IMMPs (13). These bacterial polysaccharides are clearly more difficult to digest by hydrolytic enzymes of environmental competitors (33), thus providing a competitive advantage. Also, the carbohydrate products of the GtfC enzymes from non-lactic-acid bacteria may have such roles, but a function in protecting E. sibiricum and E. antarcticum cells against the freezing temperatures of their habitats cannot be excluded either.…”
Section: Figmentioning
confidence: 99%
“…Additional samples were taken after 1, 2, 3, 4, 5, and 6 h for soluble substrates, and 0, 24, 48, 72, 96, and 120 h for granular substrates. Samples of 1 μl were analyzed on TLC (Merck, Darmstadt, Germany) and run overnight using a butanol, ethanol, water (5:5:3 v/v/v) running buffer, and stained using 40% sulfuric acid and 5% Orcinol (9,10-dihydrophenanthrene) in methanol5354.…”
Section: Methodsmentioning
confidence: 99%